Prevalence of Epileptiform Discharges in Children with Sensori-Neural Hearing Loss and Behavioral Problems Compared to Their Normal Hearing Peers - AMIRSALARI, Susan; RADFAR*, Shokoufeh; AJALLOUYEAN, Mohammad; SABURI, Amin; YOUSEFI, Jaleh; NOOHI, Sima; TAVALLAIE, Seyed Abbas; HASSANALIFARD, Mahdieh; GHAZAVI, Yasaman (Iranian Journal of Child Neurology, 2014)
<!--[if gte mso 9]> 800x600 <![endif]--> How to Cite This Article: Amirsalari S, Radfar Sh, Ajallouyean M, Saburi A, Yousefi J, Noohi S, Tavallaie SA, Hassanalifard M, Ghazavi Y. Prevalence of Epileptiform Discharges in Children with Sensori-Neural Hearing Loss and Behavioral Problems Compared to Their Normal Hearing Peers. Iran J Child Neurol. 2014 Spring 8(2):29-33. Objective Overactivity and behavioral problems are common problems in children with prelingually profound sensorineural hearing loss (SNHL). Data on epileptiform electroencephalography (EEG) discharges in deaf children with psychological disorders are so limited. The primary focus of this study was to determine the prevalence of epileptiform discharges (EDs) in children with SNHL and overactivity or behavioral problems. Materials & Methods A total of 262 patients with prelingually profound SNHL who were referred to our cochlear implantation center between 2008 and 2010 were enrolled in this study. Children with SNHL who had diagnosis of overactivity and/or behavioral problems by a pediatric psychiatrist, underwent electroencephalography (EEG). EEG analysis was carried out by a board-certified pediatric neurologist. The control group consisted of 45 cases with overactivity or behavioral problems and normal hearing. Results One hundred thirty-eight children with mean age of 3.5±1.23 year were enrolled in the case group, of whom 88 cases (63.7%) were boy. The control group consisted of 45 cases with mean age of 3.2±1.53 years, of whom 30 (66.6%) cases were male. EDs were detected in 28 (20.02%) children of the case group (with SNHL) in comparison with 4 (8.88%) in the control group (without SNHL), which was statistically significantly different. Conclusion In this study, we obtained higher frequency of EDs in deaf children with overactivity and/or behavioral problem compared to the children without SNHL. Further studies are required to evaluate the possible association of SNHL with EDs in overactive children. References 1. Matsuura M, Okubo Y, Toru M, Kojima T, He Y, Hou Y, et al. A cross-national EEG study of children with emotional and behavioral problems: a WHO collaborative study in the Western Pacific Region. Biol Psychiatry 1993;34(1-2):59-65. 2. Hindley P, Kroll L. Theoretical and epidemiological aspects of attention deficit and overactivity in deaf children. J Deaf Stud Deaf Educ 1998;3(1):64-72. 3. [No author listed] . Clinical practice guideline: diagnosis and evaluation of the child with attentiondeficit/ hyperactivity disorder. American Academy of Pediatrics. Pediatrics 2000;105(5):1158-70. 4. Klinkerfuss GH, Lange PH, Weinberg WA, O’Leary JL. Electroencephalographic abnormalities of children with hyperkinetic behavior. Neurology 1965;15(10):883-91. 5. Millichap JJ, Stack CV, Millichap JG. Frequency of epileptiform discharges in the sleep-deprived electroencephalogram in children evaluated for attention-deficit disorders. J Child Neurol 2011;26(1):6-11. 6. Fonseca LC, Tedrus GM, Moraes C, Vicente Machado A, Almeida MP, Oliveira DO. Epileptiform abnormalities and quantitative EEG in children with attentiondeficit/ hyperactivity disorder. Arq Neuropsiquiatr 2008;66(3A):462-7. 7. Venkatesh C, Ravikumar T, Andal A, Virudhagirinathan BS. Attention - deficit/Hyperactivity Disorder in Children: Clinical Profile and Co-morbidity. Indian J Psychol Med 2012 ;34(1):34-8. 8. Monastra VJ, Lubar JF, Linden M. The development of a quantitative electroencephalographic scanning process for attention deficit-hyperactivity disorder: reliability and validity studies. Neuropsychology 2001;15(1):136-44. 9. Monastra VJ, Lubar JF, Linden M, VanDeusen P, Green G, Wing W, et al. Assessing attention deficit hyperactivity disorder via quantitative electroencephalography: an initial validation study. Neuropsychology 1999; 13(3):424-33. 10. Barry RJ, Johnstone SJ, Clarke AR. A review of electrophysiology in attention-deficit/hyperactivity disorder: II. Event-related potentials. Clin Neurophysiol 2003;114(2):184-98. 11. Magee CA, Clarke AR, Barry RJ, McCarthy R, Selikowitz M. Examining the diagnostic utility of EEG power measures in children with attention deficit/hyperactivity disorder. Clin Neurophysiol 2005;116(5):1033-40. 12. Loo SK, Barkley RA. Clinical utility of EEG in attention deficit hyperactivity disorder. Appl Neuropsychol 2005;12(2):64-76. 13. Venkateswaran S, Shevell M. The case against routine electroencephalography in specific language impairment. Pediatrics 2008;122(4):e911-6. 14. Amirsalari S, Ajallouyean M, Saburi A, Haddadi Fard A, Abed M, Ghazavi Y. Cochlear implantation outcomes in children with Waardenburg syndrome. Eur Arch Otorhinolaryngol 2012; 269(10):2179-83. 15. Amirsalari S, Yousefi J, Radfar S, Saburi A, Tavallaie SA, Hosseini MJ, et al. Cochlear implant outcomes in children with motor developmental delay. Int J Pediatr Otorhinolaryngol 2012;76(1):100-3. 16. Holtmann M, Becker K, Kentner-Figura B, Schmidt MH. Increased frequency of rolandic spikes in ADHD children. Epilepsia 2003;44(9):1241-4. 17. Richer LP, Shevell MI, Rosenblatt BR. Epileptiform abnormalities in children with attention-deficithyperactivity disorder. Pediatr Neurol 2002;26(2):125-9. 18. Socanski D, Herigstad A, Thomsen PH, Dag A, Larsen TK. Epileptiform abnormalities in children diagnosed with attention deficit/hyperactivity disorder. Epilepsy Behav 2010;19(3):483-6. 19. Fonseca LC, Tedrus GM. [Somatosensory evoked spikes and epileptiform activity in “normal” children]. Arq Neuropsiquiatr 2003;61(3B):793-5. [Article in Portuguese] 20. Borusiak P, Zilbauer M, Jenke AC. Prevalence of epileptiform discharges in healthy children--new data from a prospective study using digital EEG. Epilepsia 2010;51(7):1185-8. 21. Daneshi A, Hassanzadeh S. Cochlear implantation in prelingually deaf persons with additional disability. J Laryngol Otol 2007;121(7):635-8. 22. Dye MW, Bavelier D. Attentional enhancements and deficits in deaf populations: an integrative review. Restor Neurol Neurosci 2010;28(2):181-92. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Calibri","sans-serif"; mso-bidi-font-family:Arial;} --> <!--[endif] -->